Determining Attitudes of Nursing Students on Premarital Sex - Nursel Alp Dal; Kerime Derya Beydağ (Güncel Hemşirelik Araştırmaları Dergisi)
Objective: Sexual attitudes and behaviors are mainly affected by parents at early ages, and then peer influence becomes more important. During college years, less parental control and cultural environment of universities have significant effect on sexual attitudes and behaviors. It was aimed in this study to determine nursing students' attitudes of premarital sex and to reveal the factors affecting it. Method: The descriptive study was conducted between December 2018 and December 2019 with the Nursing Department students attending a foundation university providing education in the Anatolian side of Istanbul. The population of the study consisted of 284 nursing students who were attending the school on the specified dates. No sample selection was made in the study and it was aimed to reach the whole population. However, the study was completed with 260 students due to the fact that there were students who did not want to participate in the study and the incomplete surveys were not included in the study. An introductory survey form and Premarital Sex Attitude Scale (PMSAS) were used to obtain the data. Results: The students' mean score of PMSAS was found to be 52.44±14.32 It was determined that those between the ages of 18-20 and those whose hometown was in the eastern region had a more negative attitude towards premarital sex (p